A new volatile antimicrobial agent-releasing patch for preserving fresh foods. (December 2018) - Rozenblit, Boris; Tenenbaum, Guy; Shagan, Alona; Corem Salkmon, Enav; Shabtay-Orbach, Ayelet; Mizrahi, Boaz
Highlights: A patch that can be loaded and thereafter release volatile antimicrobial oils. Microcrystalline cellulose exhibited the highest level of absorption. Carvacrol and tea tree oil patches exhibited marked antibacterial activity. Carvacrol oil showed the strongest protective effect. This system may be fitted to all types of currently used packages. Abstract: Active packaging that releases antibacterial volatile oils has been one of the most promising approaches to protecting fresh food and increasing its shelf life. Existing strategies, however, are limited by the need to adjust packaging material to suit the particular antimicrobial and environmental conditions. Here we describe a new patch made of absorbent polymers and two volatile antimicrobial compounds, carvacrol and tea tree oil (TTO). After assessing several different polymers, microcrystalline cellulose was chosen as the absorbent matrix due to its high level of absorption, around 90% of its weight. Carvacrol and TTO were released into the head compartment in a controlled manner, reaching a plateau within 20 min. Both carvacrol and TTO patches exhibited marked antimicrobial activity against Escherichia coli, Listeria monocytogenes, Alternaria alternate, Penicillium commune and moderate activity against Pseudomonas putida . Visual and mechanical evaluation of strawberries and pumpkin specimens showed that carvacrol patches had the best effect on increasing shelf life compared to TTO and empty patches. The versatility of the patch, the simplicity of its production and its effectiveness demonstrated here make it very attractive as a new platform to extend the shelf life of fresh foods.